2021
DOI: 10.1007/s10964-021-01432-0
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Aggressive Peer Norms in Elementary School Children’s Perceptions of Classroom Peer Climate and School Adjustment

Abstract: Although prior research has indicated that peer norms for aggression enhance the spread of aggression in classrooms, it is unclear to date how these norms relate to students’ classroom climate perceptions and school adjustment. Aggressive descriptive norms reflect the average aggression of all students in classrooms, whereas aggressive popularity norms represent the extent to which aggressive behavior relates to popularity among peers. This study examined the role of aggressive descriptive and popularity norms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 55 publications
(87 reference statements)
0
6
0
Order By: Relevance
“…Peers choose peers with similarities as friends or join groups with similar characteristics based on the process of selection similarity, and the dissimilar departs from the peer group through a process of peer group pruning or deselection. [ 24 25 ]…”
Section: Discussionmentioning
confidence: 99%
“…Peers choose peers with similarities as friends or join groups with similar characteristics based on the process of selection similarity, and the dissimilar departs from the peer group through a process of peer group pruning or deselection. [ 24 25 ]…”
Section: Discussionmentioning
confidence: 99%
“…Possibly, defending signals youths' genuine care about others' safety and wellbeing, which may elicit an affectionate response among those who profit from these defending behaviors or from those who are witnesses of these behaviors. Moreover, defending behaviors may be helpful in stopping bullying (Saarento et al, 2015) and fostering a positive classroom climate (Laninga‐Wijnen et al, 2021). Therefore, defending may evoke feelings of appreciation and gratitude—not only among victims, but also among other classmates – and enhance the likability of defenders over time.…”
Section: Discussionmentioning
confidence: 99%
“…First, adolescents with high status—both in terms of being liked and being popular—may feel more confident to defend victimized peers with no fear of social repercussions from bullies, as high‐status youth generally have more friends (Laninga‐Wijnen & Veenstra, 2021), which can protect them against victimization (Hodges & Perry, 1999). Second, adolescents who are well‐liked or popular tend to be more assertive (Poorthuis et al, 2021) and have better social–emotional skills (Laninga‐Wijnen et al, 2021), allowing them to better understand the effect of their behaviors on their peers (Hawley, 2014), making them more likely to defend. Third, costly signaling theory (Grafen, 1990)—which applies mainly to popularity—proposes that people tend to behave more prosocially when they are being observed by others.…”
Section: Introductionmentioning
confidence: 99%
“…http://ijlter.org/index.php/ijlter Although previous classroom climate studies have demonstrated consistency across items within the scale, they have not uncovered other potential sources of variability that may influence the strength of agreement of students' perceptions within the classroom. Aggregate perceptions will not be reliable if each student gives a different perception (Laninga-Wijnen et al, 2021;Verlie & Blom, 2022). This is different from the perception of students in the class who have similarities or agreements.…”
Section: Introductionmentioning
confidence: 92%
“…Based on a conceptual basis, classroom climate is a predictor of students' level of knowledge and skills in a particular field. One of the reasons for increasing students' knowledge and skills is students' comfort in the classroom climate so that they are encouraged to express ideas in class discussions (Bayram Özdemir & Özdemir, 2020;Laninga-Wijnen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%